X-ray irradiation induces subtle changes in the genome-wide distribution of DNA hydroxymethylation with opposing trends in genic and intergenic regions. Issue 1 (2nd January 2019) - Becker, Benjamin V.; Kaatsch, Leonhard; Obermair, Richard; Schrock, Gerrit; Port, Matthias; Ullmann, Reinhard
ABSTRACT: DNA hydroxymethylation has gained attention as an intermediate in the process of DNA demethylation. More recently, 5-hydroxymethylcytosine has been recognized as an independent epigenetic mark that can persist over time and that exerts influence on gene regulation and other biological processes. Deregulation of this DNA modification has been linked to tumorigenesis and a variety of other diseases. The impact of irradiation on DNA hydroxymethylation is poorly understood. In this study we exposed lung fibroblasts (IMR90) to 0.5 Gy and 2 Gy of X-rays, respectively. We characterized radiation induced changes of DNA hydroxymethylation 1 h, 6 h, 24 h and 120 h after exposure employing immunoprecipitation and subsequent deep sequencing of the genomic fraction enriched for hydroxymethylated DNA. Transcriptomic response to irradiation was analyzed for time points 6 h and 24 h post exposure by means of RNA sequencing. Irradiated and sham-irradiated samples shared the same overall distribution of 5-hydroxymethylcytosines with respect to genomic features such as promoters and exons. The frequency of 5-hydroxymethylcytosine peaks differentially detected in irradiated samples increased in genic regions over time, while the opposing trend was observed for intergenic regions. Onset and extent of this effect was dose dependent. Moreover, we demonstrated a biased distribution of 5-hmC alterations at CpG islands and sites occupied by the DNA binding protein CTCF. In summary, our study provides new insights into the epigenetic response to irradiation. Our data highlight genomic features more prone to irradiation induced changes of DNA hydroxymethylation, which might impact early and late onset effects of irradiation.